ANALISIS ATAS BELANJA MODAL PADA KABUPATEN DAN KOTA DI SUMATERA SELATAN - Periansya periansya; Ardiyan Natoen; Susi Ardiani; Fadilia Nouvanti; Gian Prasetyo; Melani Dwi Safitri (JURNAL RISET TERAPAN AKUNTANSI, 2020)
This study examines the effect of local taxes, levies, and balance funds on capital spending. This research uses samples obtained from 17 districts/cities in South Sumatra Province in 2015-2019. This research is quantitative, and this research also uses secondary data as the data source. This data collection uses the documentation method where the data obtained from the Regional Expenditure Revenue Realization Report (APBD) on the official website http://www.djpk.kemenkeu.go.id/. Data analyzed with multiple linear regression using software (SPSS). This study indicates that local taxes, levies, and balance funds simultaneously positively and significantly affect capital expenditures with a determination coefficient of 77.2%. Then local taxes, local levies, and balance funds have a positive impact on capital spending to increase the community's welfare.     Keywords: Local Taxes, Regional Levies, Balancing Funds, Capital Expenditures.